Pemanfaatan Artificial Intelligence dalam Ketidakjujuran Akademik Mahasiswa Akuntansi: Perspektif Fraud Hexagon - Aysah, Putri; Hatta, Madani; Fela, Suci Fenti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The use of Artificial Intelligence (AI) technology in the academic sector not only presents benefits but also introduces new risks, one of which is the potential misuse for committing academic dishonesty. The objective of this study is to examine how academic dishonesty among accounting students, specifically involving the use of AI as an aid in fraudulent activities, is influenced by the six components of the fraud hexagon: pressure, opportunity, rationalization, capability, arrogance, and collusion. In this context, AI is employed as a tool to facilitate cheating, such as fully copying AI-generated outputs or utilizing it during examinations. This research employs a quantitative methodology, with data collected through an online survey administered to Indonesian accounting students using purposive sampling. IBM SPSS Statistics 25 software was used to conduct multiple linear regression analysis on the data. The findings indicate that there is no positive effect from five factors, pressure, opportunity, rationalization, capability, and arrogance on AI-based academic dishonesty. Conversely, the variable collusion demonstrates a positive effect. These findings contribute to the understanding of unethical behavior in the digital academic context and may serve as a reference for formulating ethical policies regarding AI usage in higher education institutions.